2021
DOI: 10.1108/wje-02-2021-0110
|View full text |Cite
|
Sign up to set email alerts
|

Graphene as a stimulus for mechanical strength in glass-fiber reinforced polymers composite

Abstract: Purpose The purpose of this paper is related with the comparative study between graphene-based glass fiber–reinforced polymer composites and without graphene composite on polymer matrix. The current study explains the result of amalgamation of 4 Wt.% graphene oxide (GO), in comparison to without graphene, on the mechanical strength of glass fiber/epoxy (GE). Design/methodology/approach A hand layup technique is used for the experimental study. For this, chemical synthesis process is approached based on Humme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…They reported that at 0.25 wt% loading, the elastic modulus was increased by 13% and strength by 75%. Dwivedi et al [24] prepared with and without graphene GFRP composites and concluded in their study that the fortification of 4.0 wt% of GO in epoxy matrix material showed improvement in mechanical strength and elongation by 7.46% and 12.31%, respectively. Gara et al [25] used exfoliated GO to prepare GF/epoxy composite to enhance the mechanical properties of the composite.…”
Section: Introductionmentioning
confidence: 99%
“…They reported that at 0.25 wt% loading, the elastic modulus was increased by 13% and strength by 75%. Dwivedi et al [24] prepared with and without graphene GFRP composites and concluded in their study that the fortification of 4.0 wt% of GO in epoxy matrix material showed improvement in mechanical strength and elongation by 7.46% and 12.31%, respectively. Gara et al [25] used exfoliated GO to prepare GF/epoxy composite to enhance the mechanical properties of the composite.…”
Section: Introductionmentioning
confidence: 99%